2019
DOI: 10.1103/physreve.99.052214
|View full text |Cite
|
Sign up to set email alerts
|

Logic gates on stationary dissipative solitons

Abstract: Stable dissipative solitons are perfect carries of optical information due to remarkable stability of their waveforms that allows the signal transmission with extremely dense soliton packing without loosing the encoded information. Apart of unaffected passing of solitons through a communication network, controllable transformations of soliton waveforms are needed to perform all-optical information processing. In this paper we employ the basic model of dissipative optical solitons in the form of the complex Gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…While path integrals frequently elude an exact evaluation, they are often useful to develop approximation schemes, including semiclassical treatments or instanton techniques [13][14][15]. However, the continuum limit of the coherent state path integral is mathematically subtle [16][17][18][19], and is still an area of current research [19][20][21][22][23]. In taking the continuum limit, the differentiability of trajectories is incorrectly assumed [10,13,24]; this has been reported to lead to wrong results for certain simple models [19].…”
Section: Introductionmentioning
confidence: 99%
“…While path integrals frequently elude an exact evaluation, they are often useful to develop approximation schemes, including semiclassical treatments or instanton techniques [13][14][15]. However, the continuum limit of the coherent state path integral is mathematically subtle [16][17][18][19], and is still an area of current research [19][20][21][22][23]. In taking the continuum limit, the differentiability of trajectories is incorrectly assumed [10,13,24]; this has been reported to lead to wrong results for certain simple models [19].…”
Section: Introductionmentioning
confidence: 99%
“…By exploiting the fascinating shape changing collision scenario of degenerate Manakov solitons, it has been theoretically suggested that the construction of optical logic gates is indeed possible, leading to all optical computing [27]. We also note that logic gates have been implemented using two stationary dissipative solitons of complex Ginzburg-Landau equation [29].…”
Section: Introductionmentioning
confidence: 92%
“…Individual addressing opens further interesting possibilities for the optical generation of arbitrary trains of spikes, which has potential applications in different domains, e.g. time-resolved spectroscopy, pump-probe sensing of material properties [43], generation of dense frequency combs [44][45][46][47] and all optical data processing [48,49]. As such, the possibility to generate controllable cluster of LSs using non-local effects has both fundamental and practical interests.…”
Section: Introductionmentioning
confidence: 99%